Isometric exercise as a test of pain modulation: Effects of experimental pain test, psychological variables, and sex - Naugle, Kelly M. (2013)
OBJECTIVE: Little is known regarding whether exercise-induced hypoalgesia (EIH) produced by isometric exercise is influenced by psychological factors or systematically varies across multiple experimental psychophysical pain tests. Thus, this study sought to determine the influence of experimental pain test, psychological factors, and sex on the hypoalgesic response of submaximal isometric exercise. METHODS: Healthy young males (n=12) and females (n=15) completed one training and two testing sessions consisting of quiet rest (control condition) or a 3-minute isometric handgrip performed at 25% of maximum voluntary contraction. Pain testing was conducted on both forearms prior to and following exercise and quiet rest. The pain tests included: pressure pain thresholds (PPT), suprathreshold pressure pain test, static prolonged heat test, and temporal summation of heat pain. Participants completed the Pain Catastrophizing Scale during the training session and the State-Trait Anxiety Inventory –State version prior to each session. The data were analyzed with mixed model ANOVAs, partial pearson correlations, and hierarchical regression analyses. RESULTS: Isometric exercise increased PPTs for men and women, reduced pain perception during static prolonged heat stimuli for women, and reduced temporal summation of pain for men and women. Greater pain catastrophizing was associated with smaller reductions in temporal summation following isometric exercise. CONCLUSIONS: These findings demonstrate that the hypoalgesic response to submaximal isometric exercise is partially a function of sex and experimental pain test. Furthermore, the relationship between EIH and pain catastrophizing was psychophysical pain test specific, with greater pain catastrophizing predicting diminished EIH only during the temporal summation of pain trials.